2020
DOI: 10.1590/1980-5373-mr-2020-0305
|View full text |Cite
|
Sign up to set email alerts
|

Coated Surface on Ti-30Ta Alloy for Biomedical Application: Mechanical and in-vitro Characterization

Abstract: Several studies have been carried out to develop new materials for biomedical applications. Material surfaces that present biomimetic morphology like nanotubes or nanofibers that provides nanoscale architectures have been shown to alter cell/biomaterial interactions. The coated surface biomaterial with biocompatible polymers and nanotubes of TiO 2 is an alternative to improve osseointegration. The anodization process was performed to obtain nanotubes of TiO 2 covering the Ti-30Ta alloy surface and the electros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…In addition, titanium with nanotubes promoted cell proliferation on osteoblasts after seven days. Capelatto et al [ 19 ] verified that titanium nanotube samples presented a significant effect on the number of cells present, showing an increase of cells from day 1 to day 7. The cell proliferation assay results showed that titanium nanotubes (100 nm) could promote high cell proliferation compared with control Ti [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, titanium with nanotubes promoted cell proliferation on osteoblasts after seven days. Capelatto et al [ 19 ] verified that titanium nanotube samples presented a significant effect on the number of cells present, showing an increase of cells from day 1 to day 7. The cell proliferation assay results showed that titanium nanotubes (100 nm) could promote high cell proliferation compared with control Ti [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the effectiveness of using TiO 2 nanotube-containing surfaces to increase cell proliferation has been demonstrated [ 11 , 19 ]. Titania nanotubes (TNTs) with a diameter of 100 nm were able to decrease Staphylococcus aureus attachment and simultaneously improve the mesenchymal stem cell response [ 20 ].…”
Section: Introductionmentioning
confidence: 99%